US Veterinarians' Knowledge, Experience, and Perception Regarding the Use of Cannabidiol for Canine Medical Conditions - Kogan, Lori; Schoenfeld-Tacher, Regina; Hellyer, Peter; Rishniw, Mark (Frontiers in Veterinary Science, 2019)
Due to the myriad of laws concerning cannabis, there is little empirical research regarding the veterinary use of cannabidiol (CBD). This study gauged US veterinarians’ knowledge level, views and experiences related to the use of cannabinoids in the medical treatment of dogs. Participants (n = 2130) completed an anonymous, online survey. Results were analyzed based on legal status of recreational marijuana in the participants’ state of practice, and year of graduation from veterinary school. Participants felt comfortable in their knowledge of the differences between THC and marijuana, as well as the toxic effects of marijuana in dogs. Most veterinarians (61.5%) felt comfortable discussing the use of CBD with their colleagues, but only 45.5% felt comfortable discussing this topic with clients. No differences were found based on state of practice, but recent graduates were less comfortable discussing the topic. Veterinarians and clients in states with legalized recreational marijuana were more likely to talk about the use of CBD products to treat canine ailments than those in other states. Overall, CBD was most frequently discussed as a potential treatment for pain management, anxiety and seizures. Veterinarians practicing in states with legalized recreational marijuana were more likely to advise their clients and recommend the use of CBD, while there was no difference in the likelihood of prescribing CBD products. Recent veterinary graduates were less likely to recommend or prescribe CBD. The most commonly used CBD formulations were oil/extract and edibles. These were most helpful in providing analgesia for chronic and acute pain, relieving anxiety and decreasing seizure frequency/severity. The most commonly reported side-effect was sedation. Participants felt their state veterinary associations and veterinary boards did not provide sufficient guidance for them to practice within applicable laws. Recent graduates and those practicing in states with legalized recreational marijuana were more likely to agree that research regarding the use of CBD in dogs is needed. These same groups also felt that marijuana and CBD should not remain classified as Schedule I drugs. Most participants agreed that both marijuana and CBD products offer benefits for humans and expressed support for use of CBD products for animals.